Human chromosome atlas : introduction to diagnostics of structural aberrations - Behrend, Claudia; Hagh, Javad Karimzad; Mehdipour, Parvin; Schwanitz, Gesa (Springer, 2017)
This atlas presents the results of cases of structural chromosome aberrations based on the currently available methods of analysis for different types of abnormality. It particularly focuses on which spectrum should be chosen when combining the different techniques to achieve the best method of diagnosis in individual cases, for example direct preparation of cells and mitoses, short or long-time cell culture, fluorescence in situ hybridization (FISH), analysis of interphases, microarray or DNA sequencing. Generally it has to be taken into account, that the development of new and improved investigation methods is forthcoming. Thus, by improvement of diagnostic possibilities new fields of investigation arise, and special groups of patients with cytogenetic analyses can be re-analysed under new research questions.
Keywords: Human chromosomes -- Atlases.; elektronické knihy; electronic books